(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2024)
COVID-19 had profound socioeconomic effects at the global level. The article analyzes the transformations in Quevedo, Ecuador, after the pandemic, focusing on local households. A mixed methodology was used with a sample of 600 households, combining surveys, interviews and focus groups. Results revealed a significant decrease in household income and a 30 % increase in labor informality. Rural areas were most affected, with a 78 % reduction in income. Resilience strategies included the use of savings, community support and self-employment. Public policies were perceived as insufficient, highlighting the need for more targeted approaches. The importance of designing policies that consider local realities was emphasized. The study provided a basis for future research and postpandemic public policies.